1994 State Cigarette Excise Tax Threats, ADAMHA, Smoking Restrictions 1994 Local Preemption Legislation (Tufts Archival Research Center, 2007)
Maps of the United States. Codes states in terms of 1994 state cigarette excise tax threats, smoking restrictions 1994 local preemption legislation, and ADAMHA compliance.